Вплив війни на цивільних людей в Україні: зростання тривожності - Милютін, О. Є. (ХНУРЕ, 2024)
The deterioration of mental health and increased anxiety is a significant challenge and problem that needs to be addressed. Solving this problem requires a comprehensive approach: professional psychological and psychiatric care, informing the population about security issues, forming communities of support, self-help, institutional efforts, etc
Keywords: зростання тривожності; вплив війни на цивільних людей